Measuring and evaluating KM capability in an organization: An exploratory case study. Issue 2 (6th May 2014) - Basu, Bhaskar; Kumar Ray, Pradip
Abstract : Purpose: – The purpose of this paper is to validate through a case study involving an organization in India, a five-phase Define-Identify-Build-Assess-Review methodology proposed for designing and implementing knowledge management capability (KMC) in an organization from a holistic perspective. Design/methodology/approach: – This paper adopts the case study approach, using semi-structured interviews and survey questionnaires to gauge KMC in the organization. Exploratory factor analysis and multiple regressions are applied to determine the impact of the chosen factors on KMC of the organization. Further, interpretive structural modelling is used to determine impact of selected variables on the business performance. Findings: – KMC of the organization is predominantly based on the "embedded routines", "knowledge base" and its "shared utilization" in the organization. The KMC is primarily driven through improved learning and rich explicit knowledge. Research limitations: – The study is confined to a specific business process in the organization. As the focus of study is based on a single organization, the generalization of the results to other organizations needs to be proven. Practical implications: – The periodical monitoring of the identified KMCs leads to enterprises making corrections and adjustments on the knowledge assets accordingly. Originality/value: – Introspection of the KMCs of the organization by the management in a holistic manner and bridging the operational gap by developing performance metrics.